Effects of two workload-matched high intensity interval training protocols on regulatory factors associated with mitochondrial biogenesis in the soleus muscle of diabetic rats - Delfan, Maryam; Vahed, Alieh; Bishop, David J.; Amadeh Juybari, Raheleh; Laher, Ismail; Saeidi, Ayoub; Granacher, Urs; Zouhal, Hassane (Frontiers in Physiology, 2022)
Aims: High-intensity interval training (HIIT) improves mitochondrial characteristics. This study compared the impact of two workload-matched high-intensity interval training (HIIT) protocols with different work: recovery ratios on regulatory factors related to mitochondrial biogenesis in the soleus muscle of diabetic rats. Materials and methods: Twenty-four Wistar rats were ramdomly divided into four groups : non-diabetic control, diabetic control (DC), diabetic + 4-5 × 2-min running at 80-90% of the maximum speed reached with 2-min of recovery at 40% of the maximum speed reached (DHIIT1:1), and diabetic + 5-6 × 2-min running at 80-90% of the maximum speed reached with 1-min of recovery at 30% of the maximum speed reached (DHIIT2:1). Both HIIT protocols were completed five times/week for four weeks while maintaining an equal running distances in each session. Results: Gene and protein expressions of PGC-1α, p53, and citrate synthase were increased in the muscles of the DHIIT1:1 and DHIIT2:1 groups compared to DC (p˂0.05). All parameters, except for PGC-1α protein (p=0.597), were higher in DHIIT2:1 than in DHIIT1:1 (p˂0.05). Increases in the maximum speed reached were observed in both DHIIT groups, but occurred to a greater extent in the DHIIT2:1 group than in the DHIIT1:1 group. Conclusions: Our findings indicate that both HIIT protocols can potently up-regulate gene and protein expression of PGC-1α, p53, and CS. However, DHIIT2:1 has superior effects than DHIIT1:1 in improving mitochondrial adaptive responses in diabetic rats.